Avaliação da contaminação da alface (Lactuva sativa) variedade crespa por bactérias e enteroparasitas - Pereira, Julio Abrantes (2010)
The search for a healthy diet consisting of vegetables consumed "in natura" just exposing the population to the risk of infections by bacteria and intestinal parasites. This study aimed to assess the bacteriological and parasitological of lettuce (Lactuca sativa) commercialized in supermarkets and public markets in João Pessoa-PB, comparing the quality of which are sold in supermarkets with the public markets. In this study 40 heads of lettuce, including 20 from four supermarkets and 20 from four public markets were submitted to two washes with sterile water, and subjected to bacteriological and parasitological analysis. Analyses showed that all samples had total coliforms but did not have Salmonella that 30% had fecal coliform above 1x102 MPN/g, and that intestinal parasites were present in 85% of vegetables, including Strongyloides spp., Giardia spp., E. histolytica / E. dispar. In public markets were found higher levels of bacterial contamination than the supermarkets (p > 0,05), but these two establishments showed no significant difference in the contamination with intestinal parasites. Due high contamination observed becomes necessary to establish laws limiting the presence of these contaminants so that the lettuce does not serve as a vehicle disseminator of disease by bacteria and intestinal parasites.